Developmental programming: impact of testosterone on placental differentiation - Beckett, EM (2014)
Gestational testosterone (T) treatment causes maternal hyperinsulinemia, intra-uterine growth retardation (IUGR), low birth weight, and adult reproductive and metabolic dysfunctions. Sheep models of IUGR demonstrate placental insufficiency as an underlying cause of IUGR. Placental compromise is likely the cause of fetal growth retardation in gestational T-treated sheep. This study tested if T excess compromises placental differentiation by its androgenic action and/or via altered insulin sensitivity. A comparative approach of studying gestational T (aromatizable androgen) against dihydrotestosterone (DHT; non-aromatizable androgen) or T plus androgen antagonist, flutamide, was used to determine whether the effects of T in placental differentiation were programmed by its androgenic actions. Co-treatment of testosterone with the insulin sensitizer, rosiglitazone, was used to establish whether the effects of gestational T on placentome differentiation involved compromised insulin sensitivity. Parallel cohorts of pregnant females were maintained for lambing and the birth weight of their offspring was recorded. Placental studies were conducted on days 65, 90, or 140 of gestation. Results indicated that 1) gestational T treatment advances placental differentiation, evident as early as day 65 of gestation, and culminates in low birth weight, 2) placental advancement is facilitated at least in part by androgenic actions of T and is not a function of disrupted insulin homeostasis, and 3) placental advancement, while helping to increase placental efficiency, was insufficient to prevent IUGR and low birth weight female offspring. Findings from this study may be of relevance to women with PCOS, whose reproductive and metabolic phenotype is captured by the gestational T-treated offspring.